2015
DOI: 10.1002/jor.22996
|View full text |Cite
|
Sign up to set email alerts
|

Identifying clinically meaningful benchmarks for gait improvement after total hip arthroplasty

Abstract: There are no established benchmarks for gait mechanics after total hip arthroplasty (THA). This study sought to identify minimum clinically important postoperative (MCIP) or minimum clinically important improvement (MCII) values for self-selected walking speed, sagittal plane dynamic hip range of motion (HROM) (peak flexion-peak extension) and peak hip adduction moments measured during quantitative gait analysis. Preoperative and 1-year postoperative data collected during quantitative gait analysis, along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
42
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 53 publications
3
42
1
2
Order By: Relevance
“…However, because the preoperative range of motion was actually larger in the nonresponders, the result was that nonresponders had similar postoperative sagittal plane range of motion and lower flexion moments than nonresponders. It is important to note, however, that neither group (on average) achieved the minimum clinically important value for hip range of motion recently proposed, and that the range of motion for both groups was at the lower end of values generally reported for people after THA (30 − 40°) . Sagittal plane ROM for control subjects in the literature ranges from ∼38° to 51°) .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, because the preoperative range of motion was actually larger in the nonresponders, the result was that nonresponders had similar postoperative sagittal plane range of motion and lower flexion moments than nonresponders. It is important to note, however, that neither group (on average) achieved the minimum clinically important value for hip range of motion recently proposed, and that the range of motion for both groups was at the lower end of values generally reported for people after THA (30 − 40°) . Sagittal plane ROM for control subjects in the literature ranges from ∼38° to 51°) .…”
Section: Discussionmentioning
confidence: 78%
“…Function can be objectively and specifically characterized using quantitative gait analysis. Many studies have shown that gait mechanics do not fully return to normal after THA . However, work linking gait mechanics to clinical outcomes is still emerging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Future work in this area may lead to benchmarks for postoperative strength, such as those previously proposed for postoperative gait mechanics. 44 A somewhat surprising finding was that on average, these participants were not more fatigued than a general population of US adults. We expected, based on the OA literature, that subjects in this study would report significant levels of fatigue.…”
Section: Discussionmentioning
confidence: 93%
“…Future work in this area may lead to benchmarks for postoperative strength, such as those previously proposed for postoperative gait mechanics. 44 …”
Section: Discussionmentioning
confidence: 99%